2020
DOI: 10.1136/bmjopen-2019-034763
|View full text |Cite
|
Sign up to set email alerts
|

Distance as a barrier to obstetric care among indigenous women in Panama: a cross-sectional study

Abstract: ObjectivesWe assess the relationship between distance to a woman’s assigned health clinic and obstetric care utilisation.DesignWe employ a cross-sectional study design using baseline data from the evaluation of a conditional cash transfer programme to promote greater utilisation of maternal and infant health services. Data were collected between December 2016 and January 2017.SettingThe study is conducted in Ngäbe Buglé, the largest of Panama’s three indigenous territories, where maternal mortality is three ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Long distances leading to long travel hours contribute to a lack of immediate access to medical facilities since available hospitals are located relatively far from the people who need them, leading to delay in care [69]. Previous research has evaluated the effect of distance as a barrier to care leading to delay, which yielded similar results to those of our study [70][71][72][73][74].…”
Section: Discussionsupporting
confidence: 76%
“…Long distances leading to long travel hours contribute to a lack of immediate access to medical facilities since available hospitals are located relatively far from the people who need them, leading to delay in care [69]. Previous research has evaluated the effect of distance as a barrier to care leading to delay, which yielded similar results to those of our study [70][71][72][73][74].…”
Section: Discussionsupporting
confidence: 76%
“…International studies have highlighted the association between physical barriers to access and use of obstetric health care equipment ( 19 , 20 ) . A study with 6,655 African women (Burkina Faso) showed that those who lived further away were significantly less likely to give birth in a health unit ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudos internacionais têm evidenciado a associação entre barreiras físicas de acesso e uso dos equipamentos de atenção à saúde obstétrica (19,20) . Estudo com 6.655 mulheres africanas (Burkina Faso) evidenciou que as que viviam mais longe eram significativamente menos propensas a parir em unidade de saúde (19) .…”
Section: Discussionunclassified